2008
DOI: 10.1038/ki.2008.401
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sodium chloride and volume depletion in the chronic kidney disease of congenital chloride diarrhea

Abstract: Congenital chloride diarrhea is due to mutations in the intestinal Cl(-)/HCO(3)(-) exchange (SLC26A3) which results in sodium chloride and fluid depletion leading to hypochloremic and hypokalemic metabolic alkalosis. Although treatment with sodium and potassium chloride offers protection from renal involvement in childhood, the long-term renal outcome remains unclear. Here we describe two cases of congenital chloride diarrhea-associated end-stage renal disease with transplantation. Further, we show that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 51 publications
1
51
0
1
Order By: Relevance
“…Absorptive and secretory processes for oxalate along the nephron could participate in determining urinary oxalate excretion, but the contribution of DRA to this is likely to be minimal, as it is frequently not detected in renal tissues. DRA expression has only been reported for the human kidney (43), whereas studies with mouse (37; unpublished observations), rat (3), and rabbit (24) renal cortex failed to detect the Slc26a3 gene product. The impact of intestinal DRA on oxalate homeostasis in humans does not appear to be as dramatic as seen here in mice, since Cl Ϫ -losing diarrhea patients have been reported to have a median daily excretion ratio of oxalate to creatinine of 0.012 (43), which is similar to that reported (30) for a population of healthy adults (0.016).…”
Section: Dra Mediates Oxalate and CLmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorptive and secretory processes for oxalate along the nephron could participate in determining urinary oxalate excretion, but the contribution of DRA to this is likely to be minimal, as it is frequently not detected in renal tissues. DRA expression has only been reported for the human kidney (43), whereas studies with mouse (37; unpublished observations), rat (3), and rabbit (24) renal cortex failed to detect the Slc26a3 gene product. The impact of intestinal DRA on oxalate homeostasis in humans does not appear to be as dramatic as seen here in mice, since Cl Ϫ -losing diarrhea patients have been reported to have a median daily excretion ratio of oxalate to creatinine of 0.012 (43), which is similar to that reported (30) for a population of healthy adults (0.016).…”
Section: Dra Mediates Oxalate and CLmentioning
confidence: 99%
“…Urinary oxalate excretion in KO mice was 30% of that measured in WT mice, highlighting the contribution of transcellular intestinal absorption to oxalate homeosta- sis. Since there is little evidence for a significant presence of the DRA protein in renal tissues (43), the reduction of oxalate excretion in DRA KO mice is most likely associated with the decrease in intestinal absorption. Finally, DRA KO mice exhibited a 60% reduction of serum oxalate, which was significantly lower than in the controls.…”
mentioning
confidence: 99%
“…In addition, it has been shown that butyrate is also able to inhibit both basal and adenosine 3_,5_-cyclic monophosphatestimulated Cl_ secretion in a dose-dependent manner [41]. Finally, the trophic effects elicited by short chain fatty acids on intestinal mucosa (mediated through circulatory, hormonal, and neural mechanisms) could contribute to improvement in diminishing severity of diarrhea in the CLD patient [37,41].…”
Section: Oral Butyratementioning
confidence: 99%
“…It is easily administered, useful in preventing severe dehydration episodes, and may be a promising therapeutic approach for a long-term treatment in this rare and severe condition [37].…”
Section: Oral Butyratementioning
confidence: 99%
See 1 more Smart Citation